Gym and swim: a co-facilitated exercise program that improves community connection, confidence, and exercise habits in a community mental health service - Sophie Forlico; Andrew Baillie; Kate Keys; Peter Woollett; Georgia Frydman; Andrew Simpson (Discover Mental Health)
Abstract High rates of cardiometabolic disease and poor physical health outcomes contribute to significant premature mortality in people living with severe mental illness (PLWSMI). Lifestyle interventions such as exercise are known to improve both physical and mental health outcomes, however the best way to deliver exercise programs for PLWSMI remains a challenge. This paper uses a pragmatic program evaluation of a co-delivered low-cost community-based exercise program implemented over a 6-month period. Of 46 referrals in the first half of 2023 to the SLHD Gym and Swim program, 13 gave consent to participate in standardised measures and qualitative interviews. Findings revealed an increase in average hours of sport/exercise, improvements in confidence to exercise independently and within group settings, as well as achievement of individualised goals. The success of the program was in part due to the co-facilitation between peer support workers and exercise physiologists, community connection and the established partnership between the public health service and the local government council. Results offer evidence to adopt and implement accessible and low-cost exercise opportunities in the community external to health services to address barriers of attendance for PLWSMI.